Health Information Quality and Patient Safety Performance: A Study at Awet Muda Narmada Regional Hospital - Syamsuriansyah, Syamsuriansyah; Hizriansyah, Hizriansyah (Journal of Health and Nutrition Research, 2025)
This study examined the relationship between health information quality management and patient safety performance, identifying significant factors influencing safety outcomes. A quantitative approach was used, with the Hospital Survey on Patient Safety Culture (HSPSC) translated, culturally tailored, and validated for the local setting. The intervention consisted of comprehensive training in information quality, workflow alignment, and the implementation of standardized documentation procedures over 6 weeks. The study was conducted at Awet Muda Narmada Regional General Hospital in West Lombok, West Nusa Tenggara, Indonesia, with a sample size of 92 healthcare professionals, including physicians, nurses, and health information managers. The results demonstrated a 46-point improvement (from 52 to 98 on a 100-point Likert-type scale) in the dimension of "Management Support for Patient Safety," with an average gain of 46 points after the intervention.  A paired t-test found a significant difference between pre- and post-intervention scores (p = 0.001), and linear regression confirmed a strong positive relationship between information quality and patient safety (y = 0.86x + 24.15), with a coefficient of determination (R²) of 0.496. The study demonstrates that improving health information quality is associated with better patient safety outcomes. Practical implications include the need to incorporate information technology training, create non-punitive incident reporting systems, and optimize Electronic Health Records (EHR) to foster a stronger patient safety culture in hospital settings.